Effects of agricultural grade nutrient modulation on the biomass production and carbon fixation rate of Isochrysis sp. microalgae - Rashid, Nurfilza Zaheera Muhammad Nor; Radzun, Khairul Adzfa; Saharuddin, Aimi Nadia; Rusmidi, Muhamad Helmi Husaini; Ismail, Asmida; Razak, Wan Razarinah Wan Abdul; Pardi, Faezah; Ismail, Khudzir; Jawad, Ali H; Yahya, Liyana (Asian Journal of Agriculture and Rural Development, 2023)
This study looked at what happens when the nutrients in agricultural grade (AG) medium are changed and how that changes the biomass production and CO2 fixation ability of Isochrysis sp. It aims to address the challenges in establishing biofuel stocks due to the microalgae issue. A medium optimization system (AMOS) was first used to determine the optimum level of nitrogen, phosphorus, and micronutrients in AG medium using Factorial and Box Behnken Experimental Design, which resulted in improvements to N, K, Ca, Mg, Fe, and Z with 15 mM, 10 mM, 0.5 mM, 0.8 mM, 0.3 mM, and 0.15 mM, respectively. Subsequently, the improved medium was tested in a 1L culture volume, resulting in a 2.37 gL-1 biomass extracted from cultivation in the improved AG medium compared to cultivation in the traditional F/2 medium (1.63 gL-1). Cultures with higher Ca and Fe tested in an interim study yielded 9% and 7% enhanced biomass production compared to AG medium. The new optimized medium, which is known as TNBR-optimized medium (OM), was tested at the live coal-fired power plant in a 250 L air-lift bubbling column-type photobioreactor supplied with simulated and actual flue gas. The TNBR-optimized medium has demonstrated better algae growth, especially on actual flue gas, which has increased the concentration of CO2. The improved CO2 fixation rate was 0.72 gCO2.L-1 day-1, respectively, against those obtained from the previous report – 0.52 gCO2 L-1 day-1. An improved medium has been formulated to cultivate Isochrysis sp., and the current work can be further utilized for larger-scale cultivations.